2008
DOI: 10.1186/1297-9686-40-5-467
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological characterisation of the Ankole Longhorn cattle in the African Great Lakes region

Abstract: -The study investigated the population structure, diversity and differentiation of almost all of the ecotypes representing the African Ankole Longhorn cattle breed on the basis of morphometric (shape and size), genotypic and spatial distance data. Twentyone morphometric measurements were used to describe the morphology of 439 individuals from 11 sub-populations located in five countries around the Great Lakes region of central and eastern Africa. Additionally, 472 individuals were genotyped using 15 DNA micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 29 publications
8
21
4
Order By: Relevance
“…HG and mean HW of Ankole cows were higher than previous studies (e.g. Ndumu et al, 2008), possibly because of variation in the sampling frame and sample sizes used between the studies. HW in this study was also higher than data reported for other Sanga breeds (Payne and Hodges, 1997).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…HG and mean HW of Ankole cows were higher than previous studies (e.g. Ndumu et al, 2008), possibly because of variation in the sampling frame and sample sizes used between the studies. HW in this study was also higher than data reported for other Sanga breeds (Payne and Hodges, 1997).…”
Section: Discussioncontrasting
confidence: 71%
“…Ankole are one such cattle and are kept under pastoralism and crop-livestock systems (Lamwaka, 2006;Wurzinger et al, 2007). Ankole cattle also exist in other countries of the African great lakes region such as Burundi, Rwanda, Tanzania (Ndumu et al, 2008) and Democratic Republic of Congo. Both male and female Ankole cattle have similar features, with the exception of a hump, which exists only in the adult males.…”
Section: Introductionmentioning
confidence: 99%
“…The current analysis highlights the importance of body measurements to differentiate among cattle groups and breeds in West Africa (Table 2). Differences in body shape between the main cattle types analysed in the current study (taurine and zebu) are due to major differences in origin (independent domestication events; Chen et al, 2010;Pérez-Pardal et al, 2010a, b), but also due to breeding differences. West African humped zebu cattle are always larger and are bred in the northern arid Sahel while native West African taurine cattle are small sized (and even dwarf; see mean values for Lagounaire cattle in Table 2) and bred in the humid southern Soudano-Guinean agroecological area.…”
Section: Discussionmentioning
confidence: 84%
“…Studies aiming at morphological assessment in cattle are relatively scant in cattle and mainly performed on adult females (Mwacharo et al, 2006;Bene et al, 2007;Ndumu et al, 2008). Although information on body measurements in White Fulani cattle (related with Zebu Peul) exists (Yakubu et al, 2009), mean values computed for the same body traits cannot be straightforwardly compared with our study due to differences in sampling strategies: a significant part of the individuals sampled by Yakubu et al (2009) were less than 2.5 years old and, therefore, were probably still growing.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers have been widely used to evaluate the genetic diversity of indigenous cattle breeds (FAO, 2011). Genetic diversity has been investigated in a number of developing countries on breeds such as the Ankole longhorn (Ndumu et al 2008;Kugonza et al 2011) and Afrikaner cattle breeds (Pienaar et al 2014) as well as a number of indigenous cattle breeds in Mozambique (Bessa et al 2009), Cuba (Acosta et al 2013), Cameroon (Ngono-Ema et al 2014 and India (Sharma et al 2015).…”
Section: Introductionmentioning
confidence: 99%